2015
DOI: 10.1007/s12015-015-9610-z
|View full text |Cite
|
Sign up to set email alerts
|

Nuclear Mechanics and Stem Cell Differentiation

Abstract: Stem cells are characterized by their self-renewal and multi-lineage differentiation potential. Stem cell differentiation is a prerequisite for the application of stem cells in regenerative medicine and clinical therapy. In addition to chemical stimulation, mechanical cues play a significant role in regulating stem cell differentiation. The integrity of mechanical sensors is necessary for the ability of cells to respond to mechanical signals. The nucleus, the largest and stiffest cellular organelle, interacts … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 60 publications
(140 reference statements)
0
13
0
Order By: Relevance
“…It has been suggested that chromatin density might itself act to regulate gene expression in a stem-cell population [65]. While the embryonic stem-cell state has a chromatin organization that is best described as a highly correlated fluid, the differentiated state fluctuates far less, with condensed heterochromatin foci forming during the differentiation of pluripotent embryonic stem cells [66]. The formation of heterochromatin domains has recently been argued to be mediated by phase separation [39,40].…”
Section: Discussionmentioning
confidence: 99%
“…It has been suggested that chromatin density might itself act to regulate gene expression in a stem-cell population [65]. While the embryonic stem-cell state has a chromatin organization that is best described as a highly correlated fluid, the differentiated state fluctuates far less, with condensed heterochromatin foci forming during the differentiation of pluripotent embryonic stem cells [66]. The formation of heterochromatin domains has recently been argued to be mediated by phase separation [39,40].…”
Section: Discussionmentioning
confidence: 99%
“…The mechanical behaviour of the nucleus and its role in cellular mechanotransduction depends on multiple factors, including its own makeup and that of its environment. Intrinsically, the expression of laminA/C (type V intermediate filaments) and the organization of chromatin are believed to determine the mechanical properties of the nucleus 1 . Externally, cytoskeletal networks, notably actin, have also been suggested to play a key role in nuclear state and mechanics 2 .…”
Section: Introductionmentioning
confidence: 99%
“…While the embryonic stem call state has a chromatin organization that is best described as a highly correlated fluid, the differentiated state fluctuates far less, with condensed heterochromatin foci forming during the differentiation of pluripotent embryonic stem cells (Mao et al, 2015). The formation of heterochromatin domains has recently been argued to be mediated by phase separation (Larson et al, 2017;Strom et al, 2017).…”
Section: Discussionmentioning
confidence: 99%